Pulsed ion beam induced changes in a topography of the surface layers of VT1-0 and VT6 titanium alloy; Energy Fluxes and Radiation Effects (EFRE-2016) - Zhidkov M. Mihail; Kolobov Yu. Yuri; Ligachev A. Alexandr; Potemkin G. V. Gely Valerjyanovich; Remnev G. E. Gennady Efimovich (2016, 2016)
Title screen